Strategi Pendampingan Sosial Aceh Barat P2TP2A Terhadap Korban Kekerasan Seksual Pada Anak - Anwar, Anwar; Baihaqi, Baihaqi; Aja Dahniar, Aja Dahniar; Jailani, Jailani (Prodi Pengembangan Masyarakat Islam STAIN Teungku Dirundeng Meulaboh, 2022)
Children are a mandate from Allah SWT that we must protect in order to achieve a period of growth and development to become adults who have a sustainable future in the nation's future. Child sexual violence is an act committed by an adult against a child under 18 years of age, including a child who is still in the womb. The aims of this study were: To find out the description of cases of sexual violence against children in West Aceh, to find out the social assistance strategy carried out by P2TP2A in West Aceh Regency for child victims of sexual violence, to find out what are the factors that support and hinder the implementation of social assistance to child victims of sexual violence. The approach used is a qualitative approach. Data collection techniques with interviews, observation and documentation. Data analysis techniques use interactive methods which include: reduction, data presentation and drawing conclusions. The subjects in this study were heads of P2TP2A child protection, P2TP2A child protection heads, P2TP2A child protection counselors, victims of sexual violence, and the community. From the research that has been done, it can be concluded that: The P2TP2A social assistance strategy for child victims of sexual violence, includes: policy changes through observation, conducting legal services, and counseling assistance, factors that support carrying out social assistance to child victims of sexual violence, namely: the presence of professional companions and cooperation between institutions, factors that hinder the implementation of social assistance to child victims of sexual violence, namely: insufficient funds, lack of victim data and lack of human resources (HR).